From the Internet of Things to the Objectification of the Human Being: Sociopolitical Construction of Technology and a Critique of Society 5.0 - Cahit Bağcı (Journal of Economy Culture and Society)
The Japanese government announced Society 5.0 on November 7, 2016 as a development project with the goal of a technology-themed and human-centered society with the aim of improving human lives. Japan explained the main mission of this program as facilitating and serving human life through technology and contributing to a comfortable and long life. This announcement discussed the organic bond between Industry 4.0 and Society 5.0; the goals of Society 5.0; the aspects affecting, changing, and transforming individuals and society within this framework; the new relationship networks and cultural elements; and their impact on values and meaning, individualization, and objectification of the individual. Since the inception of the idea of panopticon, the control, inspection, and surveillance of public and social order have been treated as a culturally romantic and engineering critique of technology in the connection of the power-individual relationship. This article examines if Society 5.0 will be able to accomplish a postmodern structure through a new culture (i.e., acculturation). In the search for answers to these questions, this article analyzes the situations that would occur in place of human relations and the structures that will be changed in the targeted social order.